Acute exposure to boron in Nile tilapia (Oreochromis niloticus): Median-lethal concentration (LC50), blood parameters, DNA fragmentation of blood and sperm cells. (December 2018) - Acar, Ümit; İnanan, Burak Evren; Zemheri, Fahriye; Kesbiç, Osman Sabri; Yılmaz, Sevdan
Abstract: Recently, Boron (B) contamination of aquatic ecosystem has received considerable critical attention due to its toxic effects at high concentrations on plants as well as animals. Previous studies on toxic effects of B have not dealt with DNA damages in blood and sperm cells of Nile tilapia ( Oreochromis niloticus ), together with blood parameters. This study consisted of two successive experiments purposes to determine these findings, including the median-lethal concentration (LC50 ) of B for Nile tilapia. In the first one, at 96 h, LC50 of B for Nile tilapia was 141.42 mg L −1 B. In the second one, Nile tilapia were treated with five elevated B concentrations (1, 5, 25, 50 and 100 mg L −1 B) and hematological, serum biochemical parameters, and DNA damages of Nile tilapia in these treatments were determined comparing with the control after 14 days of exposure. Hematological parameters (red blood cell count, hematocrit, and hemoglobin) were similar to each other in all groups while serum biochemical parameters (glucose, total protein, cholesterol, alkaline phosphatase, glutamic oxaloacetic transaminase, and glutamic pyruvic transaminase) in B treatments, especially in 50 and 100 mg L −1 B groups, were found significantly higher (P < 0.05). DNA fragmentation was detected in all blood cells in ≥25 mg L −1 B treatments, while all sperm cells in 100 mg L −1 B treatments. These results demonstrated the harmful effects of B at high concentration (50 and 100 mg L −1 B) on the DNA integrity of blood and sperm cells, and also the serum biochemical parameters. Graphical abstract: Highlights: Boron (B) had a 96 h LC50 of 141.42 mg/L for the Nile tilapia ( Oreochromis niloticus ). No differences were found in hematological parameters. Blood serum biochemical parameters were highly affected by 50 and 100 mg B/L. Acute exposure of B could cause DNA damages in blood and sperm cells of O. niloticus. Blood cells were more vulnerable than sperm cells to B exposure.